Analysis of Soil Subscription on Soil Lack Combination of PVD and PHD With Analytical and Numerical Methods Using 3D Plaxis in STA 103 + 550 Construction of High Click Toll Road Range, Stage 1 - Ardi I. P. Sagala (International Journal of Social Service and Research, 2022)
The construction of transportation facilities on soft soil will cause problems where the bearing capacity of soft soil is low and the process of land subsidence will require a long period of time. As is known, the land subsidence factor causes many problems in the process of building transportation facilities, besides that, there will also be problems at the level of service (serviceability). Therefore, this problem must be anticipated before the transportation facility begins to function. There are many methods that can be done. Where in the selection of methods, the efficiency and effectiveness factors are very dominant. One method that can be done is to fill the soil combined with vertical drain and horizontal drain. This method was chosen to be one of the most widely used methods because it is easy to do and quite efficient. The purpose of writing this thesis is to analyze thereduction of settlement each layer of soft soil that is repaired using the soil filling method combined with prefabricated vertical drain and prefabricated horizontal drain using the PLAXIS 3D program. The results of this calculation will then be compared with observations made in the field using a settlement plate for later analysis. Calculation of the size of the consolidation settlement using the Terzaghi 1 dimension consolidation method obtained a decrease of 16.09 cm. This result is relatively close to the results of observations made in the field of 16.3 cm. In the PLAXIS 3D modeling approach using 1 PVD line and 1 PHD line, the result is a decrease of 16.52 cm without taking into account the effect of the smear zone and 16.22 cm taking into account the effect of the smear zone. In the PLAXIS 3D modeling approach using 2 PVD lines and 2 PHD lines, the result is a decrease of 16.54 cm without taking into account the effect of the smear zone and 16.28 cm by taking into account the effect of the smear zone. And when modeling without using PHD the value of the decrease obtained is 9.7 cm. When modeling using sand blanket as a substitute for PHD, the decrease value is 13.3 cm